2006
DOI: 10.1176/ajp.2006.163.5.932
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory Identification Deficits in First-Episode Psychosis May Predict Patients at Risk for Persistent Negative and Disorganized or Cognitive Symptoms

Abstract: UPSIT scores can be used to identify patients at risk for persistent negative and disorganized/cognitive symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(24 citation statements)
references
References 9 publications
(5 reference statements)
1
22
0
Order By: Relevance
“…Performance deficits on the UPSIT in SZ have been shown to be related to negative symptoms (Brewer et al, 1996; Stedman and Clair, 1998; Brewer et al, 2001; Malaspina and Coleman, 2003; Corcoran et al, 2005; Good et al, 2006; Moberg et al, 2006; Ishizuka et al, 2010) and to be valence-dependent. Kamath et al (2011d) report that odor identification accuracy on the UPSIT in people with SZ patients is impaired due to errors in identifying pleasant and neutral odors compared to controls, with no group difference in ability to correctly identify unpleasant odors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Performance deficits on the UPSIT in SZ have been shown to be related to negative symptoms (Brewer et al, 1996; Stedman and Clair, 1998; Brewer et al, 2001; Malaspina and Coleman, 2003; Corcoran et al, 2005; Good et al, 2006; Moberg et al, 2006; Ishizuka et al, 2010) and to be valence-dependent. Kamath et al (2011d) report that odor identification accuracy on the UPSIT in people with SZ patients is impaired due to errors in identifying pleasant and neutral odors compared to controls, with no group difference in ability to correctly identify unpleasant odors.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, there are several studies that report a relationship between dysfunction in odor identification and negative symptoms in SZ (Brewer et al, 1996; Stedman and Clair, 1998; Brewer et al, 2001; Coleman et al, 2002; Malaspina and Coleman, 2003; Corcoran et al, 2005; Good et al, 2006; Moberg et al, 2006). Specifically, the deficit syndrome (Carpenter et al, 1988) has been found to be associated with poor performance on the UPSIT (Malaspina et al, 2002; Malaspina and Coleman, 2003; Moberg et al, 2006; Strauss et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…nicotine) on odor identification (Brewer et al, 1996; Malaspina and Coleman, 2003; McLean et al, 2004). A relationship between dysfunction in odor identification and negative symptoms of SZ has also been described (Brewer et al, 1996; Brewer et al, 2001; Coleman et al, 2002; Corcoran et al, 2005; Good et al, 2006; Malaspina and Coleman, 2003; Moberg et al, 2006; Stedman and Clair, 1998). Furthermore, deficit SZ (i.e., a subtype of the illness with primary, enduring negative symptoms) has been found to be associated with a particularly poor performance on the UPSIT (Malaspina and Coleman, 2003; Malaspina et al, 2002; Moberg et al, 2006; Strauss et al, 2009), indicating that deficits in smell identification could be differentially expressed in some subtypes of SZ.…”
Section: Introductionmentioning
confidence: 94%
“… References: 1 (Brewer et al, 2001); 2 (Malaspina et al, 2002); 3 (Malaspina and Coleman, 2003); 4 (Brewer et al, 2003); 5 (Szeszko et al, 2004); 6 (Corcoran et al, 2005); 7 (Rupp et al, 2005a); 8 (Rupp et al, 2005b); 9 (Ugur et al, 2005); 10 (Roalf et al, 2006); 11 (Good et al, 2006); 12 (Moberg et al, 2006); 13 (Strauss et al, 2009). …”
Section: Figmentioning
confidence: 99%
“…CrespoFacorro and colleagues 17 found individuals with schizophrenia to demonstrate impairment in apprecia tion of both positive and negative olfactory hedonic ex tremes, with evidence of accompanying neural circuitry dys function, and smell identification deficits have also been linked to diminished social drive in this population. 18 Good and colleagues 19 proposed smell identification test (SIT) per formance in patients with early psychosis as a prospective marker for an illness course characterized by negative and cognitive/disorganized symptoms for those with lower scores versus anxiety/depressive symptoms for those with better scores. This suggests that brain impairments associated with SIT deficits are distinct from those producing anxiety/ depression and that individuals with psychosis may have a course impacted by one of the singular symptom domains.…”
Section: J Psychiatry Neurosci 2015;40(6)mentioning
confidence: 99%